Effective Treatment of Refractory Chronic Spontaneous Urticaria with Add-On Omalizumab and Ciclosporin: From Guideline to Real-Life Practice - Trakanwittayarak, Suphattra; Kiratiwongwan, Rungsima; Tuchinda, Papapit; Chularojanamontri, Leena; Kulthanan, Kanokvalai (Archives of Clinical and Medical Case Reports, 2020)
Chronic spontaneous urticaria (CSU) is characterized by the presence of wheals and/or angioedema that occurs daily or almost daily at least two times per week for more than 6 weeks. More than 30% of patients with moderate to severe CSU are affected for longer than 5 years. Here, we report a patient with recalcitrant CSU whose symptoms were completely controlled with omalizumab and added-on ciclosporin. A 56-year-old Thai female presented at the Siriraj Urticaria Clinic with recurrent wheals and sporadic angioedema for 20 years. Her previous medication included desloratadine 20 mg/day, fexofenadine 720 mg/day, ranitidine 300 mg/day, and intermittent systemic corticosteroids, all of which failed to control her symptoms. We added ciclosporin 100 mg twice per day (3 mg/kg/day). One week later, our patient decided to discontinue ciclosporin by herself due to a worsening of her wheals, pruritus, and dyspnea. We then added omalizumab subcutaneous injection (150 mg at the beginning, 300 mg at 2 weeks, and 300 mg at 4 weeks) with no significant improvement. We decided to re-prescribe add-on ciclosporin 100 mg twice per day (3 mg/kg/day) together with subcutaneously injected omalizumab 300 mg every 2 weeks. After two months, this combination treatment led to complete symptom control, and prednisolone could be discontinued. Omalizumab in combination with ciclosporin for treatment of refractory CSU resulted in a markedly positive clinical response.